Peningkatan Kapasitas Masyarakat dalam Pengelolaan Limbah Organik dan Anorganik melalui Teknologi Biopori dan Pemanfaatan Sampah Plastik sebagai Media Tanam di Desa Kembang Karang Daya Lombok Timur - Endang Purnama Dewi; Sirajuddin Haji Abdullah; Joko Sumarsono; Asih Priyati; Reza Kusuma Nurrohman; Sapitri Mustika Sari (Universitas Mataram, 2026)
The issue of organic and inorganic waste remains a major challenge in Kembang Karang Daya Village, East Lombok Regency. Most residents do not yet sort their waste at the source, so organic and plastic waste is still disposed of or burned directly. This community service activity aims to improve the community’s knowledge and skills in source-based waste management through the application of biopore technology and the use of plastic waste as a growing medium for seedlings. The methods employed included an initial survey, outreach, training, technology transfer, mentoring, and activity evaluation. The activity involved the residents of Kembang Karang Daya Village, focusing on converting kitchen waste into compost through biopore infiltration holes and utilizing used plastic bottles as growing media for horticultural plants. The results of the activity demonstrated an increase in participants’ understanding of waste sorting and household waste management. The community was able to independently create and operate biopore holes and utilize plastic waste as a productive growing medium. This activity contributed to reducing the volume of household waste, improving environmental quality, and supporting the concepts of a circular economy and sustainable agriculture at the village level